Polymer Conjugated Gold Nanoparticles in Biomedical Applications - Anniebell, Stanley; Gopinath, Subash C.B. (Current Medicinal Chemistry, 2018)
Background: Research interest on the properties of polymer conjugated gold nanoparticle (GNP) in biomedicine is rapidly rising because of the extensive evidences for their unique properties. In the field of biomedicine, GNPs have been widely used because of their inertness and low levels of cytotoxicity. Therefore, when exposed to cells, they are less prone to exert damaging effects. GNPs are capable of being functionalized as desired and are ideal as they do not encourage undesired side reactions that might counter react with the intention of the functionalization. Biofouling is an occurrence that takes place at cellular and biological molecular level, binds non-specifically on the detection surface and forms a wrong output. This undesired incidence can be avoided by conjugating the surface of biomolecules with polymers. Densely packed repeating chains of polymers such as polyethylene glycol are capable of decreasing non-specific reactions. Applications of polymer conjugated GNPs in the field of biomedicine are as biosensors, delivery and therapeutic agents. Conclusion: Therefore, the properties and applications of polymer conjugated GNPs are studied widely as overviewed here.
Keywords: biomedical applications